RELATIVE BARGAINING STRENGTH AND ILLEGALITY Uniting Reformed Church, De Doorns v President of the Republic of South Africa 2013 (5) SA 205 (WCC) - Robert Sharrock (Obiter, 2014)
The South African courts have recognized that the relative situation of contracting parties when concluding the contract – the strength of their bargaining positions relative to each other – is a relevant factor when determining whether a particular provision in the contract (or the contract as a whole) is contrary to public policy. However, there are relatively few cases in which the court has actually relied upon inequality of bargaining power as a ground for holding that a contractual provision is illegal. In Uniting Reformed Church, De Doorns v President of the Republic of South Africa (2013 (5) SA 205 (WCC) (the “URC case”)), Zondi J held that one of the reasons why a clause common to certain notarial leases was contrary to public policy was because the contractants had not occupied equal bargaining positions when entering into the leases. Whether or not one fully agrees with the judge’s reasoning, the decision underscores the importance of understanding what is meant by relative bargaining strength and how and when it affects the lawfulness of a contract.